Plan exportador para comercializar bioambientadores de aire en la ciudad de Hamburgo- Alemania, desde Cali valle del cauca para la empresa Biagcol Ltda. (2013)
In this paper, we attempt to formulate a plan to commercialize Bio-air fresheners exporter of natural air, which does not contain chemicals that harm the environment as other similar products that are in the market, because this product is composed in a fifty percent (50 %) of guava as its main subject. This product is developed by the company Biagcol Ltda. (Bio-air fresheners to basis of guava Colombia Ltda. ), which is located in the city of Santiago de Cali - Valle del Cauca, account with the registration as an exporter to the National Directorate of Taxes and Customs, DIAN. To advance export activities, and has decided to specialize in the production and marketing of natural air fresheners on the basis of guava to national and international level feeling attracted by the market of the European Union in particular in the city of Hamburg (Germany), due to the agreements with the account between Colombia and Germany, which would allow to enter the market with some tariff preferences. The following Plan to commercialize Bio-air fresheners exporter of air in the city of Hamburg, Germany, from Cali - Valle del Cauca, is performed in order to trace the path that he must travel through the organization toward the success. Analyzes the current situation, in order to fix the paths of action that will facilitate the exploitation of the opportunities and the elusive, elimination or reduction of foreseeable risks, doing more easy to evaluate proposals and help identify markets; development requires both the knowledge of the own capacities as opportunities in the international market; knowledge on which applies the intelligence, cunning and daring to distinguish, accept and deal with the challenges, means opening new markets and leverage the potential of the business.